The useful of Animation Media TPACK-Based in Economic Subject Material to Build Critical Thinking Ability - Dila Azhari; Samsidar Tanjung; Anita Yus (Randwick International of Education and Linguistics Science Journal, 2024)
This study aims to analyze the feasibility, practicality, and effectiveness of TPACK-based animated media on economic activity material to improve critical thinking skills of grade IV students at UPT SPF SDN 101774 Sampali. This media development uses the 4D (four-D) research model, which includes the define, design, develop, and disseminate stages. The research subjects consisted of material expert validators, media experts, teachers, and 30 students. Data collection techniques in this study by conducting unstructured interviews with teachers and students and questionnaire sheets consisting of questionnaire sheets for media experts, material experts, grade IV teachers, and students. The analysis technique used in this research is product feasibility test analysis, product effectiveness test analysis, and product practicality test analysis. The developed media proved to be feasible, practical, and effective as learning media. Validation results from material experts showed 84% (feasible) at stage I and 90% (very feasible) at stage II, while validation from media experts showed 98% (very feasible) at stage I. The practicality test for teachers and students showed an average percentage of practicality of 92.6% from students and 92% from teachers, with an overall average of 92.3% (very practical). Finally, the effectiveness test of TPACK-based animated media in improving students' critical thinking skills has increased significantly, with a pretest score of 48 and increased during the post test of 86 and the results of the gain test show a value of 0.73 which is categorized as high. Thus, the TPACK-based animation media developed is declared feasible, practical, and effective for use in improving students' critical thinking skills and can be used as a new breakthrough in the utilization of digital technology in 21st century learning because this media not only utilizes technology to improve the quality of learning, but also integrates pedagogy and content relevant to the needs of today's students.